-15+3=-2(x+7)

Simple and best practice solution for -15+3=-2(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15+3=-2(x+7) equation:


Simplifying
-15 + 3 = -2(x + 7)

Combine like terms: -15 + 3 = -12
-12 = -2(x + 7)

Reorder the terms:
-12 = -2(7 + x)
-12 = (7 * -2 + x * -2)
-12 = (-14 + -2x)

Solving
-12 = -14 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-12 + 2x = -14 + -2x + 2x

Combine like terms: -2x + 2x = 0
-12 + 2x = -14 + 0
-12 + 2x = -14

Add '12' to each side of the equation.
-12 + 12 + 2x = -14 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = -14 + 12
2x = -14 + 12

Combine like terms: -14 + 12 = -2
2x = -2

Divide each side by '2'.
x = -1

Simplifying
x = -1

See similar equations:

| 1996+43x=3716 | | 3x+3=(x+3) | | 10(a-2)=-70 | | -86=-7n+4(-n-5) | | 7-3x-5-3x=5 | | Kx-3x=-2+5k | | 360-76= | | -8-14v=314 | | 5(-x-3)=5 | | 16x+34x+24x=370 | | 9(n+12)=144 | | 180-76= | | -3(x-7)=2(3x-5) | | 28=2+2a | | 2(x-8)-5(x+6)=2 | | -3x+21=6x-10 | | 4a-3b+2c= | | 100=4r | | M+(-19)=40 | | 6x+6=9x-6 | | (ab+4a+-6)+(ab+6)= | | 7(b+2)-13b=2(b-1)+6 | | 585.00+0.13x=525.00+0.21x | | x^2-2x+y^2-2y-3=0 | | X^3+7x-x-7=0 | | 2x-6=2(2-8)+10 | | 2x+6=y+4 | | 2x^2+-4x=0 | | 525.00+0.21x=585 | | 3x-2(5y-6)=8 | | 10(z+3)=5(z-8) | | 5-(x+3)=10 |

Equations solver categories